PEMANFAATAN WEBSITE RAHARJA.AC.ID SEBAGAI MEDIA INFORMASI DAN UPLOAD ARTIKEL UNTUK NS-CCIT MENGGUNAKAN FRAMEWORK YII - Indri Handayani; Ary Budi Warsito; Singgih Aji Pangestu (CCIT Journal, 2017)
The telecommunication world’s development, who’s keep on moving rapidly have create a developed innovation and creativity to also keep on moving along with the technological information’s development. Now, in Raharja University, a new program has been born which is called NSCCIT, its a National Seminar and Call for Paper who’s now have been built as a place to discuss the result of a research through a seminar. Seminar is a scheduled forum of a group of people to scientifically discuss about a topic with the purpose to grow and to manage the skills, scientific act and professionalism act through a more objective understanding about a topic which is going to be evaluated. With the creation of the NSCCIT’'s research or national seminar and Call of Paper, the result is expected to be a best solution for the civitas academica to communicate and discuss the problems which is going to be researched and help each other in solving the problems. The main purpose of this research is to develop a web database based system on raharja.ac.id website to make the spreading process of seminar's schedule information more easily using the PHP and MySQL’s technology and also implemented as an information’s conveyor media about the seminar’s schedule which is going to be held.